Managing Innovation in `Localities of Learning' in Berlin and Seville - Sascha Brinkhoff; Lech Suwala; Elmar Kulke (Innovation and Creativity in Emerging Economic Spaces, 2015)
This paper aims to contribute to the academic discussion in “Innovation and Creativity in Emerging Economic Spaces” in various aspects. First, we discuss the interdependences of innovative businesses with scientific institutions in neo- Marshallian industrial districts or `localities of learning'. Second, we integrate the concept of knowledge network management to the scale of territorial innovation networks. Here, we distinguish between substantial, relational and topical modes of operation. Ultimately, the analysis adds to our understanding on how topical `knowledge cluster management' instruments, in terms of an activated `ba', supporting the building of distinct natures of proximity and consequently promoting localized learning and innovation in territorial innovation systems (TIS) such as science parks.
Keywords: D83; L24; O32; O33; O36; R58; 330; Science and Technology Parks; Knowledge Management; Innovation; Knowledge Cluster Management; Regional Development; Territorial Innovation Systems; Relational and Topical Spaces